ANALISIS FENOMENA PERTEMUAN ANTARA DUA LAUTAN DALAM AL-QUR’AN DAN RELEVANSINYA DENGAN KEHIDUPAN MODERN - Munawar, Ali Mahfuz; Intang, Nur Halisha; Taufiqurrohmah, Nabila (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
The phenomenon of the meeting of two seas, as mentioned in the Qur'an, particularly in Surah Ar-Rahman: 19-20 and Surah Al-Furqan: 53, not only illustrates natural realities but also contains scientific significance relevant to modern scientific studies. This phenomenon describes the existence of a natural barrier separating two seas with different characteristics, such as salinity and temperature, which do not mix despite their close proximity. The scientific concept of a halocline, a transitional zone between two bodies of water with differing properties, provides a deeper explanation of this phenomenon. This paper aims to analyze the phenomenon of the meeting of two seas from the perspective of the Qur'an and science. The discussion not only reveals the connection between revelation and science but also delves into the philosophical and spiritual meanings embedded in this natural phenomenon. The study finds that the phenomenon of the meeting of two seas teaches the importance of maintaining environmental balance, valuing diversity, and fulfilling humanity’s role as stewards of the earth. Additionally, this phenomenon is relevant to efforts in environmental preservation and the sustainable management of natural resources. The analysis in this paper shows that the Qur'an and modern science harmonize in explaining natural phenomena, which can inspire efforts to protect the environment and strengthen the relationship between knowledge and faith. Thus, understanding this phenomenon can reinforce faith while increasing awareness of the critical human responsibility to preserve the earth.